Unveiling Competitiveness: A Multifaceted SWOT Analysis of a High School in the Digital Education Era: Membeberkan Daya Saing: Analisis SWOT Multifaset pada Sekolah Menengah di Era Pendidikan Digital - Windarini Cahyadiana (Universitas Muhammadiyah Sidoarjo, 2023)
In the dynamic landscape of digitalized education, the imperative for educational institutions to enhance quality and nurture skilled graduates has intensified competition and challenges. This research presents a strategic analysis of strengths, weaknesses, opportunities, and threats (SWOT) for a senior high school through primary interviews with the Principal and secondary document analysis. By leveraging strengths and addressing weaknesses, the study navigates the institution toward opportunities while mitigating potential threats. The outcome underscores the transformation of the high school into a preeminent multicultural hub, illustrating the efficacy of maximizing strengths and minimizing weaknesses. Highlights: Digital Transformation: Analyzing the impact of the digital era on education and its role in fostering competitiveness. SWOT Insights: Unveiling institutional strengths, weaknesses, opportunities, and threats to formulate strategic advancements. Cultivating Multicultural Excellence: Leveraging strengths and addressing weaknesses to establish a high school as a superior multicultural educational hub. Keywords: Digital Education, Competitiveness, SWOT Analysis, Multicultural School, Quality Improvement